Exploiting Enantiopure β‐Amino Boronic Acids in Isocyanide‐Based Multicomponent Reactions. Issue 25 (4th July 2022) - Manenti, Marco; Gusmini, Simone; Lo Presti, Leonardo; Silvani, Alessandra
Abstract: Various isocyanide‐based multicomponent reactions prove to be highly reliable when β‐substituted β‐amino boronic esters are employed as the amine component, allowing the efficient synthesis of unprecedented peptidomimetics and heteroatom‐rich boron‐containing small molecules. In particular, the scope of the Ugi reaction is widely exploited, to give a family of enantiopure β‐substituted β‐amido boronates. The Ugi‐azide and the van Leusen reactions allow to joint together prominent pharmacophoric moieties, such as β‐amino boronic acids on one side, and tetrazole or imidazole rings on the other side, realizing a successful application of the molecular hybridization concept. Abstract : Isocyanide‐based multicomponent reactions (IMCRs) are demonstrated efficient for preparation of unprecedented, highly functionalized peptidomimetics and heteroatom‐rich boron‐containing small molecules. All compounds are obtained in the form of single enantiomers and easily isolated in moderate to high yields, paving the way to a more intense exploitation of IMCRs in drug discovery programs involving aliphatic boronic acids.